PENGARUH ZASKIA ADYA MECCA SEBAGAI BRAND AMBASSADOR DALAM INSTAGRAM MECCANISMOFFICIALSHOP TERHADAP BRAND IMAGE MECCANISM - Linggani Chandra Kirana; Ridha Titi Trijayanti; Yusnia Intan Sari (Jurnal Apresiasi Ekonomi, 2020)
Companies in developing their businesses have products or services that can helping build the image of the company, so it can produce a Brand Image which can be invested in the community. Nowadays, many companies choose celebrities to be the Speakpersons or Brand Ambassadors as a strategy to build Brand Image through their influence of them that can increase and attract consumers in introducing products or services. Meccanism is an online shop that uses Zaskia Adya Mecca as their Brand Ambassador. The study aims at examining whether there is an influence and how much the influence of Zaskia Adya Mecca is as Brand Ambassador on Instagram Meccanismofficialshop on the Brand Image of Meccanism. The theory used in this study are Image, Brand Image and Brand Ambassador. The research method used in this study is quantitative method. Samples were taken in this research through distributed questionnaires to 100 followers from Meccanismofficialshop with insidental sampling method. The result of this research shows that there are influences of Zaskia Adya Mecca as Brand Ambassador on Instagram Meccanismofficialshop on the Brand Image of Meccanism with contribution value by 73.8%, it means that Zaskia Adya Mecca as Brand Ambassador on Instagram Meccanismofficialshop gives very strong and positive impact on the Brand Image of Meccanism. Keywords: Image, Brand Image, Brand Ambassador.